The Nexus of Comorbid Thyroid Dysfunction, Developmental Trauma, and Marital Distress in Severe Depression: A Case Study of an Integrative Bio-Psycho-Social-Spiritual Approach - I Putu Roni Mahendra Putra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The management of major depressive disorder (MDD) is frequently complicated by the presence of medical comorbidities and profound psychosocial stressors. This complexity creates a significant risk for "diagnostic overshadowing," where one clinical issue may mask others, leading to incomplete treatment. This case report illustrates a systematic diagnostic and therapeutic pathway for a patient whose severe depression represents a confluence of biological, psychological, and social determinants. Case presentation: We present the case of a 50-year-old female with Severe Major Depressive Disorder, Recurrent Episode (F32.2), whose functional impairment was profound (GAF=40). A systematic diagnostic inquiry revealed a nexus of pathology: previously misidentified hypothyroidism (TSH > 100 µIU/mL), comorbid metabolic syndrome (BMI 31.2 kg/m², HbA1c 7.8%); a significant history of developmental trauma (Adverse Childhood Experiences Score ≥ 4); and acute, severe marital distress involving recurrent spousal infidelity. Informed consent was obtained after assessing her capacity, with family collaboration. Conclusion: The patient was managed using an integrative bio-psycho-social-spiritual framework. This multidimensional approach involved concurrent medical stabilization, psychopharmacological treatment (Sertraline), and a phase-oriented, trauma-informed psychotherapy. The integration of culturally congruent mind-body practices was essential for building the therapeutic alliance. This holistic strategy resulted in significant, quantifiable improvement in depressive symptoms (BDI-II score decreased from 32 to 18) and functional outcomes. This case underscores the necessity of a systematic, multi-domain assessment to avert clinical error and demonstrates a replicable methodology for treating complex presentations of severe depression.